Proses Penyusunan Anggaran Berbasis Kinerja dan Pengaruhnya Terhadap Pengendalian Keuangan : (Studi kasus pada Dinas Pemberdayaan Masyarakat dan Gampong Kabupaten Aceh Barat) - Nanda Saputra (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
The performance-based budgeting process is a budgeting method for the government that links each identified funding in activities with the expected results and results, including the effectiveness in delivering those results. Financial control refers to expenditure activities. And performance monitoring aims to ensure that performance meets organizational goals. The research subjects were the Department of Trade, Industry, Cooperatives and SMEs of Meulaboh, West Aceh. The purpose of this study was to determine how the performance-based budgeting process and its impact on the effectiveness of financial control. The analytical method used is a simple linear regression analysis method because this study uses one independent variable and one dependent variable. The data used is quantitative data in the form of a questionnaire. The results of this study indicate that the performance budgeting variable (x) has a significant positive effect on the financial control effectiveness variable (y). This can be seen from the simple linear regression results obtained from the equation Y = 40,401 + 0,498X which gives the understanding that if the perception of financial control is constant or zero (0), then the amount of the performance-based budget is 40.401. units. In addition, the value that represents the regression coefficient and variable X (performance budgeting) is 0.498, meaning that if financial control is increased by 1 unit, the amount of performance budgeting will also increase or increase by 0.498 units, with the opposite assumption. fixed or constant variable.